The Use of Remote Monitoring Technologies: A Review of Recent Regulatory Scientific Advices, Qualification Opinions, and Qualification Advices Issued by the European Medicines Agency - Dekker, Marieke J. H. J.; Stolk, Pieter; Pasmooij, Anna M. G. (Frontiers in Medicine, 2021)
Aims: Recently, the use of novel Remote Monitoring Technologies (RMTs) in trials has gained much interest. To facilitate regulatory learning, we evaluated Qualification Opinions (QOs) and Advices (QAs), and Scientific Advices (SAs) of the Committee for Medicinal Products for Human Use (CHMP) to gain insight in the type of devices that are intended to be used in clinical trials for supporting/submitting application for obtaining marketing authorization (registration trails) and the main recommendations of the CHMP. Methods: QOs, QAs, and SAs of the CHMP that assessed RMTs between 2013 and 2019 were eligible for our study. The following information was extracted from the documents: year of advice/opinion, device and endpoints used, type of endpoint (primary, secondary, exploratory, or safety), indication, and main recommendations of the CHMP. Results: In total 2 QOs, 4 QAs, and 59 SAs were included in our study (total of SAs between 2013 -2019 = 4054). In the SAs, accelerometers to measure activity and/or sleep parameters (n=31) were the most frequently used devices, followed by mobile applications (n=6), and glucose monitoring devices (n=6). Usually, these measures were proposed as secondary or exploratory endpoints (n=32). The main recommendations of the CHMP were related to relevance of the (novel) outcome measure; validation; precision, accuracy, sensitivity, and specificity; compliance; sampling interval; and data handling and privacy. Conclusions: Although there was a trend towards an increased use over time, the use of RMTs in registration trials is still relatively rare. In the absence of European regulatory guidance on mHealth technologies, insight in the main recommendations of the CHMP may stimulate the use of novel RMTs in a regulatory context.